(untitled) (Tribhuvan University Journal of Microbiology, 2021)
Objectives: The study was conducted to determine antimicrobial susceptibility pattern and prevalence of Extended Spectrum Beta Lactamase (ESBL) producing E. coli from fecal sample of different chicken poultry farm located at Kirtipur. Methods: The cross sectional study was conducted from November 1st 2019 to February 29th 2020. The samples were collected from 27 different poultry farms and processed at Microbiology laboratory at Trichandra Multiple Campus. Identified E. coli were subjected to antimicrobial susceptibility test by using Kirby and Bauer Disc Diffusion technique and Combined disk method was used to determine ESBL E. coli. Results: From all 27 poultry farms, E. coli was isolated from broiler (n=13), layer (n=10), and local (n=4) breeds, of which 23 (85.18%) were not registered. The chickens were fed with vitamin and calcium as growth promoter along with antibiotics; Piperacillin, Colistin and Doxycycline. Altogether 85.18% (n=23) isolates showed sensitivity towards Nitrofurantoin, Cefotaxime and Ceftazidime followed by Tigecycline 77.7% (n=21). Among these isolates 66.6% (n=18) were resistance towards Piperacillin followed by Ampicillin 37% (n=10). A statistically significant correlation was seen in resistance rate between broiler and layers. Among total isolates 37.03% (n=10) were Multi Drug Resistance (MDR) and 14.81% (n=4) were ESBL producer. Unregistered poultry farms were associated with MDR and ESBL Ec isolates. Conclusion: Unregistered poultry farms and irrational use of antibiotics has influenced development of MDR and ESBL isolates. Timely monitoring and surveillance is suggested to decrease the trend of antimicrobial resistance (AMR) in poultry system.